Development of a working mother dilemma scale - Dolor, Janett Aguiero (2002)
The process of development in Malaybalay participated in by the indigenous and migrant groups was examined and described in this study. Participant observation, interview, life histories and document analysis were the methods used to gather data. In the results, these processes/themes emerged: development as a complex process, development as an educational process, education as a channel of development, change as inherent to development, and ethnicity as a strategy for survival.